The Influence of The Biochemical Components of Marijuana on Several Systems in Human Body: Review - Ginting, Rigo; Fadjri, Corrina Lailatul; Saputra, Muhammad Wahyu; Wardani, Indah Kusuma; Sahbania, Azka Fina; Fendiyanto, Miftahul Huda; Satrio, Rizky Dwi (MUNISI: Military Mathematics and Natural Sciences, 2023)
Marijuana is a substance that has the same effect as opium, which has a decreased or altered function of consciousness, loss of taste, intoxication and can lead to addiction. History has recorded a long road to the relationship between humans and cannabis plants. Nowadays, Marijuana affects the brain, influences Genetic alveolar macrophages, sperm health, Cardiovascular system, and oral health. However, a little review discussed the effect of Marijuana on the human body even though the compound can dramatically influence almost the whole human body. Therefore, this review article is important to study the effect of Marijuana on the human body.